2002
DOI: 10.1002/mpo.1305
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics in pediatric low‐grade astrocytomas

Abstract: It appears unlikely that, for children with LGA, those with normal cytogenetics have a better prognosis than those with abnormal. Histologic grade is a better predictor of outcome than cytogenetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 24 publications
(32 reference statements)
3
11
0
1
Order By: Relevance
“…In agreement with findings in previous studies (Neumann et al, 1993;Agamanolis and Malone 1995;Roberts et al, 2001;Orr et al, 2002), the PAs and (Deshmukh et al, 2008;Jones et al, 2008;Pfister et al, 2008;Jacob et al, 2009). As it was present in both infratentorial and supratentorial PAs, the gain does not seem to be specific for tumours of a given anatomic location.…”
Section: Genome-wide Array Comparative Genomic Hybridisation (Acgh)supporting
confidence: 92%
“…In agreement with findings in previous studies (Neumann et al, 1993;Agamanolis and Malone 1995;Roberts et al, 2001;Orr et al, 2002), the PAs and (Deshmukh et al, 2008;Jones et al, 2008;Pfister et al, 2008;Jacob et al, 2009). As it was present in both infratentorial and supratentorial PAs, the gain does not seem to be specific for tumours of a given anatomic location.…”
Section: Genome-wide Array Comparative Genomic Hybridisation (Acgh)supporting
confidence: 92%
“…114 Most of these low-grade gliomas in children also show no significant change in copy number and have normal karyotypes, [115][116][117] but one consistent finding between studies was the identification of trisomy of chromosome 5 and 7 or gains of 1q. [117][118][119] The mitogen-activated protein kinase pathway activation in low-grade gliomas has been described in several studies and recently linked to duplication of the BRAF gene locus.…”
Section: Future Directions For Low-grade Gliomasmentioning
confidence: 98%
“…Interestingly, diffuse astrocytomas in children show malignant transformation in only around 10% of cases (2), while the majority (60%-70%) of these tumors in adults eventually progress to anaplastic astrocytoma or secondary glioblastoma (1,3). In addition to the WHO grade, the prognosis of low-grade astrocytoma patients depends on the tumor localization, with survival being particularly poor for diffuse brain stem astrocytomas (4). The usual first-line treatment of pilocytic and diffuse astrocytomas consists of surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic alterations frequently observed in adult anaplastic astrocytomas and/or glioblastomas, such as mutations of TP53 or PTEN, homozygous deletion of CDKN2A, amplification of CDK4 or EGFR, and losses of chromosome 10, are only rarely encountered in pediatric pilocytic and low-grade diffuse astrocytomas (5). Previous studies investigating copy number changes in these tumors have shown normal karyotypes in the vast majority of cases (4,6). Analyses of copy number changes in a total of more than 160 cases examined in different studies employing a variety of technologies revealed only a few consistent findings.…”
Section: Introductionmentioning
confidence: 99%